Optimization of Village Financial Management Strategy to Improve the Effectiveness of Village Development Programs (Case Study of Batu Putih Village, Tellu Limpoe District, Bone Regency) - Kikin Amelia Amir; Andi Rustam; Nasrullah Nasrullah (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the effect of village fund management strategies to increase the effectiveness of the village development program in Batu Putih, Tellu Limpoe District, Bone Regency. The population in this research is the village community involved in the Batu Putih village development programs, totaling 60 people. The type of research used is descriptive quantitative, the data sources used are primary and secondary data where the primary data comes from observations and questionnaires. The data analysis technique used is simple regression analysis using the Statistical Package for the Social Science (SPSS) version 20 application. The result of the research shows that village fund management (X) has a positive and significant influence on the effectiveness of village development programs (Y) seen from the result of the t count > t tabel (3,472 > 1,672) and the significant value = 0,00 < 0,05.